THE EFFECT OF EDUCATION, TRAINING, AND MOTIVATION ON THE CIVIL SERVANT PERFORMANCE AT THE CITY POPULATION AND CIVIL REGISTRATION OFFICE, EAST SERAM - Amin, Mohamad (UTSAHA: Journal of Entrepreneurship, 2023)
According to Article 1 of Law No. 43/1999, the duties of civil servants are to improve the effectiveness, efficiency, and level of professionalism in implementing their main duties and functions. The objective of this research is to determine the effect of education, training, motivation on civil servant performance at the city population and civil registration office, East Seram. Primary data was obtained using questionnaires to 57 selected respondents and interviews; and secondary data was obtained from available literature. The analytical tool used is descriptive analysis of multiple linear regression. The results of this research indicated that education, training, and motivation have a significant effect on employee performance simultaneously. In addition, education partially has a significant effect on employee performance, and training partially has a significant effect on employee performance. Moreover, motivation has a significant partial effect on employee performance, and the variation of employee performance is described by education, training, and motivation at 51.7% while 48.3% is described by other variables outside this research, such as work stress, work environment, and so on.